Modal Correspondence for Models - Barwise, Jon; Moss, Lawrence S. (Proceedings of the Amsterdam Colloquium, 1995)
This paper considers the correspondence theory from modal logic and obtains correspondence results for models as opposed to frames. The key ideas are to consider infinitary modal logic, to phrase correspondence results in terms of substitution instances of a given modal formula, and to identify bisimilar model-world pairs.